A practical introduction to index numbers - Ralph, Jeff.; O'Neill, Rob.; Winton, Joe. (Chichester, West Sussex, UK : Wiley, 2015)
"This book offers an introduction to the subject of index numbers for statisticians, economists and numerate members of the public"--
9.3 Why re-reference?9.4 Re-basing; 9.5 Chapter summary; References; Exercise H; Chapter 10: Deflation; 10.1 Value at constant price; 10.2 Volume measures in the national accounts; 10.3 Chapter summary; Exercise I; Chapter 11: Price and quantity index numbers in practice; 11.1 A big picture view of price indices; 11.2 The harmonised index of consumer prices; 11.3 UK measures of consumer price inflation; 11.4 PPI and SPPI; 11.5 PPPs and international comparison; 11.6 Quantity indices; 11.7 Gross domestic product; 11.8 Index of Production; 11.9 Index of services; 11.10 Retail sales index
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Index numbers (Economics); MATHEMATICS / Probability & Statistics / General; Index numbers (Economics); Electronic books; Electronic books